Primary sclerosing cholangitis: a case report and review of the topic - Jorge Luis González Jara; Manuel Salvador López Cárdenas; Lissette María Alegret Amador (Acta Médica del Centro, 2010)
The patient was admitted to hospital presenting an abdominal pain localized in the epigastrium, with irradiation to the left hypochondrium and a discrete jaundice; at first it was indicative of an ischemic heart disease because of the typical electrocardiographic changes it presented. After undergoing an abdominal ultrasonography, an acute cholecystitis was diagnosed. An endoscopic retrograde cholangiopancreatography was indicated. It showed an acute cholangitis, without lithiasis in the main bile duct. An endoscopic sphincterotomy was carried out. The patient underwent an emergency cholecystectomy. It was necessary to repeat the cholangiopancreatography because of the persistent jaundice and the suspicion of sclerosing cholangitis was confirmed. The patient received antibiotic treatment (ampicillin) and steroids; his general condition improved and was discharged.